In vivo toxicity of a synthetic dodecapeptide from A gliadin in patients with coeliac disease. - Mantzaris, G; Jewell, D (Informa Healthcare, 1991)
A single dose of a synthetic peptide of A gliadin (residues 206-217) sharing homology with the E1b protein of adenovirus 12 was instilled intraduodenally in two treated coeliac patients. Biopsy specimens were taken before and repeatedly up to 24 h after the instillation by means of a Quinton hydraulic multiple biopsy instrument and processed for histology, morphometry (intraepithelial lymphocyte counts, crypt-to-villus ratio), immunocytochemistry, electron microscopy, and disaccharidase assays. Two subjects with irritable bowel syndrome served as controls. In the coeliac group disaccharidase activities decreased at 24 h, and abnormalities were seen on light and electron microscopy and in morphometric measurements. The lamina propria became infiltrated with mononuclear cells after 2 h, and there was also a rise in IgA-containing cells in one patient. No such abnormalities were seen in the control group. The serum concentrations of C3, C4, and C1 esterase inhibitor remained unchanged. Thus, the dodecapeptide may be one epitope of gliadin mediating the pathogenesis of coeliac disease.